Can Reclaimed Water Be Used for Sustainable Food Production in Aquaponics? - Cifuentes-Torres, Liliana; Correa-Reyes, Gabriel; Mendoza-Espinosa, Leopoldo G. (Frontiers in Plant Science, 2021)
Aquaculture is a technology used for the production of animal protein but produces a great amount of waste that decreases productivity and adversely affects the environment. Sedimentation and filtration have been used for the treatment of the suspended fraction of these wastes although dissolved substances like nutrients can be an asset. Therefore, the management of aquaculture waste remains a challenge. Aquaponics is a technology that can eliminate dissolved N and P from aquaculture systems as they serve as nutrients for plants, which are absorbed through the roots and are incorporated into their tissues. Several reports and studies exist on the benefits of aquaponic systems for the combined production of plants and aquatic organisms and its advantages in terms of economics and environmental protection. The great majority of the studies use the wastewater from the aquatic production tanks as a source of nutrients for plants production. However, domestic or municipal wastewater is a resource that has been used extensively in other production systems such as conventional agriculture and aquaculture, yet its potential as a source of water for aquaponics has not been established. The current analysis hypothesizes that reclaimed water can be used for aquaponics. Despite the extensive use of reclaimed water in agriculture and aquaculture and the low risk to human health when properly managed, there are no academic studies that have tackled this issue. In order to overcome the generalized mistrust of the public in consuming crops irrigated with reclaimed water or fish growing in reclaimed water, it is recommended that only ornamental fish and plants would be cultivated by this method. There is an urgent need for studies to verify the safety and advantages of such cultivation technique. Finally, it is necessary to establish guidelines for the responsible use of reclaimed water in aquaponics.